Nordic Humour: A Question of Humour Socialisation? - Lundquist, Lita (Nordlit, 2023)
Starting from my former empirical studies but supplemented with fresh fictional “data” from Lars von Trier’s latest TV series Riget Exodus (2022), I first describe how Danes use humour in very characteristic ways, also in cross-cultural professional settings. Next, I explain not only Danish humour but all national humour with the notion of humour socialisation, which integrates and combines national humour with the national language on the one hand, and the specific national process of civilisation on the other hand. Moving to Nordic humour, I focus on how Danes and Swedes perceive each other’s humour, and then explain divergences between the humour of these two Nordic countries. These differences, I conclude, are the result mainly of differences in their respective civilising processes, while I am waiting and hoping for deeper comparative linguistic studies of the use of ‘humour warning signals in Danish and Swedish.